Early pregnancy teaching and training amongst obstetric trainees in a tertiary maternity hospital. (March 2022) - Rowan, A.; Hayes-Ryan, D.; Hogan, J.; Cooley, S.; Geary, M.
Abstract: Proficiency in early pregnancy assessment and management is a core component of Basic Speciality Training (BST) in Obstetrics & Gynaecology. Performance and interpretation of early pregnancy ultrasound is not formalised in Ireland, resulting in variation in exposure and experience amongst trainees. We aimed to improve trainee's knowledge and confidence in early pregnancy ultrasound. This was though a multimodel teaching program of didactic lectures, tutorials, and case-based discussions. Additionally, we organised structed assessment tests over a six-week period with a repeat revision of teaching to allow all participants attendance. All teaching was provided with facilities already available in our institution. We assessed knowledge and confidence by an anonymised survey comprising both quantitative and qualitative components pre and post training completion. We showed an improvement in knowledge, a non-significant increase was noted in mean test score in multiple choice questions relating to early pregnancy from 78.8% to 83.5% post study completion. Trainees were noted to report an increase in training during the duration of the study with 70% reporting have received little training prior to the study dropping to 13% at the end. Increased exposure to both witnessed and performed transabdominal and transvaginal ultrasound and training on the interpretation of early pregnancy ultrasound was noted. Among trainees 62% reported no formalised training in interpreting early pregnancy ultrasound at commencement reducing to 13% post study (p = 0.04). Improved confidence although non-significant was also reported among trainees. Our study demonstrates that a low-cost multimodel teaching program over a short time frame can improve knowledge, confidence and interpretation in early pregnancy ultrasound. This simple model can be easily reproduced in other institutions. As this was a pilot study, we would envision expanding it across further sites to assess its effectiveness.